Room Temperature Synthesis of Stable Zirconia‐Coated CsPbBr3 Nanocrystals for White Light‐Emitting Diodes and Visible Light Communication. Issue 10 (16th August 2021) - Mo, Qionghua; Chen, Chen; Cai, Wensi; Zhao, Shuangyi; Yan, Dongdong; Zang, Zhigang
Abstract: The photoluminescence quantum yield (PLQY) of CsPbBr3 perovskite nanocrystals (NCs) prepared by the hot‐injection method can exceed 90%, which have attracted intensive attention for white light‐emitting diodes (WLEDs). However, the whole hot‐injection experiment requires air isolation and relatively high temperature. In addition, the poor stability of CsPbBr3 NCs impedes their applications. Here, a facile method is reported to synthesize CsPbBr3 @ZrO2 NCs at room temperature in air. Owing to using ZrO2 coated CsPbBr3 NCs, the prepared CsPbBr3 @ZrO2 NCs not only present a PLQY of 80% but also exhibit an enhanced stability to heat and moisture. Furthermore, WLEDs are fabricated with CsPbBr3 @ZrO2 NCs and commercial red phosphors (CaAlSiN3 :Eu 2+ ) on blue LEDs chips. The fabricated WLEDs exhibit a correlated color temperature (CCT) of 4743 K and luminous efficacy as high as 64.0 Lm W –1 . In addition, visible light communication with a high data rate of 33.5 Mbps is achieved using the WLEDs. This work provides a room temperature strategy to coat zirconia for CsPbBr3 @ZrO2 NCs, benefiting to enhance the optical performance and stability, as well as the promotion of the great potentials in solid‐state illuminating and visible light communication applications. Abstract : A facile ZrO2 coating strategy to prepare green‐emitting CsPbBr3 @ZrO2 nanocrystals (NCs) at a room temperature, in which the tetraethoxysilane (Zr(OC4 H9 )4 ) is chosen as the precursor for the formation of ZrO2 shells. The CsPbBr3 @ZrO2 NCs exhibit enhanced optical performance and improved stability against heat and water, facilitating the applications of white light‐emitting diodes and visible light communication.